Excretion of tryptophan metabolites in Friedreich's ataxia. Issue 6 (November 1965) - Robinson, N.; Curzon, G.; Theaker, P.
Abstract : The overnight urinary excretions of the tryptophan metabolites 5-hydroxy indole acetic acid (5HIAA), indole acetic acid (IAA), indoxyl sulphate, and kynurenine were determined in 10 cases of Friedreich's ataxia and in 11 controls. Levels of 5HIAA and IAA were slightly lower and of indoxyl sulphate higher than in the controls but within normal limits; kynurenine was normal. A tryptophan load test subsequently given to four patients and three controls showed no significant abnormality in IAA, 5HIAA, indoxyl sulphate, and kynurenine. A specific abnormality in tryptophan metabolism in Friedreich's ataxia suggested by other workers was not observed.